Netflix in Web of Science: a bibliometric approach (Communication & Society, 2022)
Netflix has shaken up audiovisual industry, but what about academic research? This bibliometric analysis focuses on 210 papers indexed in Web of Science that address this issue. We examine the author, university of affiliation, language, journal, keywords, year of publication, citations received, and categories covered in WoS. We also conducted a quantitative analysis of abstracts and papers to identify the most recurrent methodologies, themes, and samples. Our results highlight a rise in Netflix studies in recent years and their tendency to analyse specific audiovisual works. There are many qualitative analysis of specific Netflix hits, but none of the shows particularly stands out. It also shows a rise in “Communication” and “Film, Radio & Television” papers (40% of them), although academic interest relies on Netflix corporate culture, business, and algorithm. These studies are mainly carried out using a qualitative methodology (83%). More than half of the articles focus on one of the Netflix series and, among them, the greatest interest lies in the representation of specific issues; gender, race and sexuality are present in 25% of the works in the sample (n=210). At the same time, among the 367 authors signing these research papers, the parity between men (51%) and women (49%) is almost absolute. It appears that the geographical and linguistic variety of papers is related to Netflix’s global expansion and that the sheer number of titles covered reveals a fleeting attention due to Netflix’s trademark: swift and concentrated consumption.